Arterial Stiffness is an Independent Risk Factor for Anemia After Percutaneous Native Kidney Biopsy - Keiko Tanaka; Masashi Kitagawa; Akifumi Onishi; Toshio Yamanari; Ayu Ogawa-Akiyama; Koki Mise; Tatsuyuki Inoue; Hiroshi Morinaga; Haruhito A. Uchida; Hitoshi Sugiyama; Jun Wada (Karger Publishers, 2017)
Background/Aims: Bleeding is the most common complication after renal biopsy. Although numerous predictors of bleeding have been reported, it remains unclear whether arterial stiffness affects bleeding complications. Method: We performed an observational study of the renal biopsies performed in our division over an approximately 6-year period (May 2010 to May 2016). The clinical and laboratory factors were analyzed to reveal the risk factors associated with bleeding, with a focus on anemia (defined as a ≥10% decrease in hemoglobin [Hb] after biopsy). The brachial-ankle pulse wave velocity (baPWV) was measured to evaluate arterial stiffness. Results: This study included 462 patients (male, n=244; female, n=218). Anemia (defined above) was observed in 54 patients (11.7%). The risk of anemia was higher in women, older patients, and patients with lower serum albumin, lower eGFR and lower diastolic blood pressure after biopsy. We then performed a further analysis of 187 patients whose baPWV data were available. Multivariate analysis revealed that a higher baPWV was an independent risk factor for anemia. ROC analysis for predicting anemia found that a baPWV value of 1839 cm/s had the best performance (AUC 0.689). Conclusion: An increased baPWV may be a more valuable predictor of bleeding than any of the other reported risk factors.